ACDL/DQ-1 calibration algorithms – Part 1: Nighttime 532 nm polarization and the high-spectral-resolution channel - F. Meng; J. Tang; G. Dai; W. Long; K. Sun; Z. Zhang; X. Song; X. Song; J. Liu; W. Chen; S. Wu; S. Wu; et al. (Atmospheric Measurement Techniques)
The Atmospheric Environment Monitoring Satellite (Daqi 1 or DQ-1) was successfully launched in April 2022, with the capability of providing continuous multi-sensor spatial and optical simultaneous observations of carbon dioxide, aerosols, and clouds. The primary payload carried on DQ-1 is an Aerosol and Carbon Detection Lidar (ACDL). The instrument comprises a high-spectral-resolution channel at 532 nm, polarization channels at 532 nm, an elastic scattering channel at 1064 nm, and an integrated-path differential absorption (IPDA) channel at 1572 nm. The optical properties of aerosols and clouds measured by the ACDL promote a quantitative characterization of the uncertainties in the global climate system; hence, precise calibrations for the ACDL are necessary. This paper outlines the algorithms employed for calibrating the nighttime 532 nm measurements for the first spaceborne high-spectral-resolution lidar with an iodine vapor absorption filter. The nighttime calibrations of the 532 nm data are fundamental to the ACDL measurement procedure, as they are utilized to derive the calibrations over daytime orbits and the calibrations of the 1064 nm channel relative to the 532 nm channel. This paper provides a review of the theoretical foundations for molecular normalization techniques as applied to spaceborne lidar measurements and includes a detailed discussion of auxiliary data and theoretical parameters used in ACDL calibrations, as well as a comprehensive description of the calibration algorithm procedure. To mitigate large errors stemming from high-energy events during calibration, a data filter is designed to obtain valid calibration signals. The paper also assesses the results of the calibration procedure by analyzing the errors of calibration coefficients and validating the attenuated backscatter coefficient results. The results indicate that the relative error of the calibrated attenuated backscatter coefficients is lower than 1 % in the calibration area, and the uncertainty of the clear-air scattering ratio was within an anticipated range of 7.9 %.